Amine sensing with distyrylbenzenes and their hexamethylene-linked polymers: spraying them on - Kumpf, Jan; Freudenberg, Jan; Schwaebel, S. Thimon; Bunz, Uwe H. F. (Macromolecules, 2014)
We herein describe synthesis and property evaluation of two aldehyde-appended nonconjugated distyrylbenzene polymers as amine sensing platforms and compare their performance to that of their monomers. The monomers and polymers were dissolved in organic solvents and spray-deposited onto silica gel and neutral alox TLC plates so as to give small strip-shaped sensor arrays. With these, differential amine detection was achieved; we find that a neutral silica gel support is better able to discern the amines than alox TLC plates.
Gesehen am 01.09.2020